Efektivitas Intensifikasi Pemungutan Pajak Bumi Dan Bangunan Perdesaan dan Perkotaan (PBB-P2) serta Kontribusinya Terhadap Pendapatan Asli Daerah (PAD) Kota Surabaya - Pradita, Ferian Dana (Jurnal Mahasiswa Perpajakan, 2014)
The enactment of the law No. 28 of 2009 about Local Taxes and Retribution, makes tax collection of Tax Property of Rural and Urban Sectors (PBB-P2) is under the authority of the Local Government. Therefore, it needs a specific to raise the realization of the target of tax revenues, especially about the PBB-P2. This condition will encourage Local Governments to further explore the potential of PAD revenue from PBB-P2 sector in the region. This research used a descriptive study with qualitative approach. The results of this study identified that the collection of PBB-P2 conducted by the DPPK of Surabaya covers only urban areas, since there is no rural area in Surabaya. Several intensification efforts of the collection Urban PBB included, maintaining and repairing of the data base, strengthening the process collection, improving supervision to tax, increasing administrative efficiency, coordinating with relevant agencies, socializing, and utilizing mobile car for PBB payments. The effectiveness of the collection of Urban PBB intensification that has been implemented by the DPPK of Surabaya showed the criteria "Adquately Effective". Urban PBB contributions from 2011 to 2013 indicating that the contribution of Urban PBB acceptance toward the realization of PAD Surabaya included in the criteria â€œMediumâ€. Keywords: Effectiveness, Intensification, PBB-P2, PAD